2007
DOI: 10.1532/hsf98.20061216
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Angiosarcoma: A Case Report

Abstract: A 32-year-old female patient presented with dyspnea and palpitation, and transthoracic echocardiography revealed the presence of pericardial effusion. Pericardiosynthesis was performed for drainage. Because of the rapid accumulation of effusion and the presence of a right atrial mass on follow-up echocardiography, a computed tomography scan was done that revealed a right atrial defect and the presence of advanced pericardial effusion. The patient was prepared for an emergency operation. The mass on the right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[1][2][3] There are only anecdotal reports of long-term survival in patients treated with surgery and adjuvant chemotherapy and/or radiotherapy. 4,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] There are only anecdotal reports of long-term survival in patients treated with surgery and adjuvant chemotherapy and/or radiotherapy. 4,9…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Although optimal treatment has not yet been established, an early diagnosis provides an opportunity for more aggressive treatment with a possibly more favorable outcome. 4,9…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown either clinical improvement or stabilization of the disease process with chemotherapy; others have demonstrated that patients treated with multimodal therapy (combination of resection, chemotherapy, and radiation) had longer survival than those treated with chemotherapy or resection alone [6,7]. A 32 year-old woman who underwent surgical resection and combination therapy was disease free at her 13th postoperative month, suggesting that advancements in multimodal therapy may prolong survival for patients and improve their overall quality of life [8].…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgical resection is the most important prognostic factor [Percy 1987;Nakamichi 1997]. There are reported cases of patients with angiosarcoma treated with only partial resection followed by chemotherapy and radiotherapy who survived 34 or even 53 months [Percy 1987;Nakamichi 1997;Olsun 2007]. In particular, preoperative chemotherapy may decrease tumor bulk and eliminate micrometastasis prior to local tumor excision.…”
Section: Discussionmentioning
confidence: 99%